Comparison between multicomponent and simultaneous dual-task exercise interventions in long-term nursing home residents: the Ageing-ONDUAL-TASK randomized controlled study. (9th October 2019) - Rezola-Pardo, Chloe; Arrieta, Haritz; Gil, Susana María; Zarrazquin, Idoia; Yanguas, José Javier; López, Maria Antonia; Irazusta, Jon; Rodriguez-Larrad, Ana
Abstract: Background: the potential benefits of dual-task interventions on older adults living in long-term nursing homes (LTNHs) from a multidimensional perspective are unknown. We sought to determine whether the addition of simultaneous cognitive training to a multicomponent exercise program offers further benefits to dual-task, physical and cognitive performance, psycho-affective status, quality of life and frailty in LTNH residents.Design: a single-blind randomized controlled trial. Setting: nine LTNHs in Gipuzkoa, Spain. Subjects: 85 men and women (ACTRN12618000536268). Methods: participants were randomly assigned to a multicomponent or dual-task training group. The multicomponent group performed two sessions per week of individualized and progressive strength and balance exercises for 3 months. The dual-task group performed simultaneous cognitive tasks to the same tasks as in the multicomponent group. Gait speed under single- and dual-task conditions, physical and cognitive performance, psycho-affective status, quality of life and frailty were measured at baseline and after 3 months of intervention. Results: both groups showed clinically significant improvements on gait performance under single- and dual-task conditions and on the short physical performance battery ( P < 0.05). Both interventions were effective in maintaining cognitive function ( P > 0.05). Only the multicomponent group significantly improved quality of life, and reduced anxiety and Fried frailty score ( P < 0.05). No group-by-time interactions were found except for the chair-stand test in favour of the multicomponent group ( P < 0.05). Conclusions: the addition of simultaneous cognitive training does not seem to offer significantly greater benefits to the evaluated multicomponent exercise program in older adults living in LTNHs.